Pengembangan Seni Karawo dalam Meningkatkan Perekonomian Masyarakat Gorontalo - Maryuni Maryuni; Kasim Yahiji; Sri Dewi Yusuf (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This article aims to elaborate the existence of karawo art development in improving the economy of the people of Gorontalo. The method used is a qualitative approach used by researchers because the data that has been collected both through observation and interviews are then described in words by first analyzing sharply the data that has been collected. The results showed that the art of karawo was considered very good so that it could improve the economy of the people of Gorontalo. Apart from being in demand by foreign and domestic tourists. Likewise, the local community shows a very good interest, they use the karawo at official (formal) events be it seminars or scientific activities, as well as at other events such as weddings, and are even used as work clothes by employees and ASN in several offices at each. Thursday. This is supported by the local government's policy of requiring ASN in the local government environment as well as promoting it through cooperation with various parties including travel agencies, as well as tourism service providers (tour guides), promotion can also be done through social media.